Personal relationships and marriage expectations: evidence from the 1998 British Household Panel Study - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2000)
The paper analyzes data on marriage expectations collected in the 1998 wave of the British Household Panel Study (BHPS) to shed light on the extent to which cohabiting unions and partnerships in which the two people live in separate residences are stable alternatives to marriage. The percentage of todays young people who will never marry appears to be around 20%. After a relatively short period, most cohabiting couples either marry or split-up and try again. Nearly three-fourths of people currently in cohabiting unions expect to marry each other and 7 out of 8 people in cohabiting unions expect to marry sometime.
Keywords: 330